Advanced fructo-oligosaccharides improve itching and aberrant epidermal lipid composition in children with atopic dermatitis - Kim, Sukyung; Kang, Bae-Gon; Sa, Soonok; Park, Se Young; Ryu, Kyungheon; Lee, Jinyoung; Park, Boram; Kwon, Mijeong; Kim, Yeonghee; Kim, Jiwon; Shin, Sanghee; Jang, Sehun; et al. (Frontiers in Microbiology, 2024)
The effects of fructo-oligosaccharides (FOS) on atopic dermatitis (AD) have not been determined. In a randomized, double-blind, placebo-controlled trial, children with AD aged 24 months to 17 years received either advanced FOS containing 4.25 g of 1-kestose or a placebo (maltose) for 12 weeks. The SCORAD and itching scores were reduced in patients treated with both FOS (all P < 0.01) and maltose (P < 0.05 and P < 0.01). Sleep disturbance was improved only in the FOS group (P < 0.01). The FOS group revealed a decreased proportion of linoleic acid (18:2) esterified omega-hydroxyceramides (EOS-CERs) with amide-linked shorter chain fatty acids (C28 and C30, all P < 0.05), along with an increased proportion of EOS-CERs with longer chain fatty acids (C32, P < 0.01). FOS may be beneficial in alleviating itching and sleep disturbance, as well as improving skin barrier function in children with AD.